Features of subsyndromal and persistent delirium - Meagher, David; Adamis, Dimitrios; Trzepacz, Paula; Leonard, Maeve (British journal of psychiatry, 2012)
Longitudinal studies of delirium phenomenology are lacking. We studied features that characterise subsyndromal delirium and persistent delirium over time. Twice-weekly evaluations of 100 adults with DSM-IV delirium using the Delirium Rating Scale-Revised-98 (DRS-R98) and Cognitive Test for Delirium (CTD). The generalised estimating equation method identified symptom patterns distinguishing full syndromal from subsyndromal delirium and resolving from persistent delirium. Participants (mean age 70.2 years (s.d. = 10.5)) underwent 323 assessments (range 2-9). Full syndromal delirium was significantly more severe than subsyndromal delirium for DRS-R98 thought process abnormalities, delusions, hallucinations, agitation, retardation, orientation, attention, and short- and long-term memory items, and CTD attention, vigilance, orientation and memory. Persistent full syndromal delirium had greater disturbance of DRS-R98 thought process abnormalities, delusions, agitation, orientation, attention, and short- and long-term memory items, and CTD attention, vigilance and orientation. Full syndromal delirium differs from subsyndromal delirium over time by greater severity of many cognitive and non-cognitive symptoms. Persistent delirium involves increasing prominence of recognised core diagnostic features and cognitive impairment.